ANALISA PENGARUH RETURN ON INVESTMENT DAN EARNING PER SHARE TERHADAP HARGA SAHAM DI PT BURSA EFEK INDONESIA - Iswati, Sri; Anggraeni, Noerlina; Yosepha, Sri Yanthy (JURNAL BISNIS & AKUNTANSI UNSURYA, 2024)
This study aims to examine the effect of return on investmen and earnings per share on stock prices. The sample of this study is the manufacturing company of the consumer goods industry sub-sector contained in the Indonesia stock exchange in the period 2013-2017 with a total of 7companiesusing the purposive sampling method.Â The analysis method used is multiple regression and hypothesis testing using t-statistics to test partial regression coefficients and f-statistics to test the significance of the effect together with the level of significance of 5% or 0.05. The sample of this study is the manufacturing company of the consumer goods industry sub-sector contained in the Indonesia stock exchange in the period 2013-2017 with a total of 7 companies using the purposive sampling method. In addition, this is also the classic assumption test which includes normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. This shows that the available data meets the requirements for using multiple linear regression models.The results of test F show that simultaneously ROI and EPS have a significant effect on stock prices, while partially with the t test it is concluded that the ROI and EPS variables do not significantly influence stock prices. The results of the coefficient of determination shown from the adjusted R-Square value of 0.067.Keywords: Return on investment, Earning per share and stock price.